An Automated Testing Approach For Pxi Chassis Software Driver - Ng , Wai Shyan (2017)
PXI chassis is a multi-vendor interoperable device, it can interconnect with many chassis, module and computer type. To make sure the device driver is able to function in specific configuration it must go through a series of testing. The complexity of PXI software testing has increased when it need to cover multiple configuration for single driver. Majority of the automated test system will execute test without have a mechanism to verify the test environment. The current trend of automated software test only execute on single test configuration, to improve the PXI chassis IVI driver test duration a test software with the capability of execute multi test configuration is developed. In order to develop this tool, a server-client concept is adopted. The advantage of server-client is to centralize the testing when multiple test system perform test at same time. The software tool client will start once completely boot in to operating system, the test system will connect to server and wait for further action from server. When server detected incoming client connection it will automatically verify and fix the testing environment, if the client fulfilled the test suite requirement it will start execute test. All clients test summary result will be feedbacked to server. The results show an average of 17.1% test duration reduction on the planned test configuration when the automated software tool applied on testing. Besides that the results suggest that execute the test on higher controller hardware performance can reduce the test duration as well.